2013
DOI: 10.1111/echo.12124
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Echocardiographic and Doppler Analysis of Coronary Artery Abnormal Origin from the Pulmonary Trunk with Mild Myocardial Dysfunction

Abstract: Noninvasive cardiovascular imaging, namely transthoracic echocardiography and Doppler specific parameters, can reach diagnosis of late presentation of ACAPA. Direct aortic implantation is a reliable and effective to establish dual coronary artery circulation and prevent risks due to myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Noninvasive cardiovascular imaging, namely transthoracic echocardiography and Doppler specific parameters, can reach diagnosis of late presentation of ALCAPA. 6 In our patient, transthoracic echocardiography revealed a prominent large ostium in the right coronary artery and multiple turbulent flow in the ventricular septum due to abundant intercoronary collaterals (so-called steal collaterals). Such echocardiographic findings should raise a high suspicion for this syndrome.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Noninvasive cardiovascular imaging, namely transthoracic echocardiography and Doppler specific parameters, can reach diagnosis of late presentation of ALCAPA. 6 In our patient, transthoracic echocardiography revealed a prominent large ostium in the right coronary artery and multiple turbulent flow in the ventricular septum due to abundant intercoronary collaterals (so-called steal collaterals). Such echocardiographic findings should raise a high suspicion for this syndrome.…”
Section: Discussionmentioning
confidence: 59%
“…Late presentation of ALCAPA is characterized by abundant development of intercoronary collaterals resulting in mild and rare symptoms, which nevertheless can cause sudden cardiac death. Noninvasive cardiovascular imaging, namely transthoracic echocardiography and Doppler specific parameters, can reach diagnosis of late presentation of ALCAPA . In our patient, transthoracic echocardiography revealed a prominent large ostium in the right coronary artery and multiple turbulent flow in the ventricular septum due to abundant intercoronary collaterals (so‐called steal collaterals).…”
Section: Discussionmentioning
confidence: 65%
“…Transthoracic echocardiography also has diagnostic value on other congenital heart diseases, including sinus of valsalva aneurysm [ 27 ], coronary sinus septal defect [ 28 ], coronary artery fistula [ 29 ], left coronary artery arising from the right pulmonary artery [ 30 ] and so on excerpt aortic coarctation.…”
Section: Discussionmentioning
confidence: 99%
“…All patients aged more than 40 years and, in contrast to this case, all had plentiful intercoronary collaterals and dilation of RCA. 12 Iriat et al showed that measurement of 2D strain is helpful in detection of subclinical ischemia in a 13-year-old patient with ALCAPA. Pulmonary artery pressure was not mentioned in their report.…”
Section: Speculations On Pathophysiology Of Ph In This Casementioning
confidence: 99%
“…Pulmonary artery pressure was not mentioned in their report. 12 Pathophysiologically, patients with ALCAPA either have the infantile type and die early because of poor intercoronary collateralization or have the adult type with adequate collateralization which enables them to survive beyond infancy 13 . This case, cannot be included in neither of these two former groups.…”
Section: Speculations On Pathophysiology Of Ph In This Casementioning
confidence: 99%